Fabrication of micro channels for titanium PEMFC bipolar plates by multistage forming process. (16th March 2021) - Xu, Zhutian; Li, Zhipeng; Zhang, Rui; Jiang, Tianhao; Peng, Linfa
Abstract: Bipolar plates made of ultra-thin titanium sheet metals feature high corrosion resistance, electrical conductivity and strength-weight ratio. They are considered as a satisfying candidate for the proton exchange membrane fuel cell (PEMFC) used in vehicles. Bipolar plates have fine and complex sub-millimeter channel features which are employed to guide the flow of hydrogen, oxygen and cooling medium, to support the reaction space, to provide sealing structure, etc. Stamping process is an efficient method to fabricate those micro features with high precision and efficiency. However, the aspect ratio of those micro features is limited by the low forming limit of titanium sheet metals. Improving the aspect ratio of metallic bipolar plates could facilitate the uniform heat and mass transfer and further improve the efficiency and performance of PEMFC. Hence a challenging issue for the stamping process of bipolar plates is how to further improve the limit aspect ratio after forming. The multistage forming process is an efficient method to increase the ultimate forming depth and the accuracy by reducing the deformation localization tendency. This work aims to investigate the applicability of that process in fabricating high-aspect-ratio micro-channels on titanium sheet metals. Single stage forming experiments of the micro channels featured with fillet radius of 0.15 mm are first conducted. It is found that the ultimate forming depth of the channels parallel to the rolling direction is 12.67% higher than in the transverse direction. Furthermore, a series of punches and dies with three different fillet radii are employed in the multistage forming process. The ultimate depth of formed channels is revealed to increase from 438.1 to 621.0 μm, i.e. the aspect ratio from 0.46 to 0.67, comparing to the single stage forming process. Hence titanium bipolar plates with a higher aspect ratio could be achieved by utilizing the presented method. The contact resistances of the samples fabricated via single and three-stage forming were further tested to find out that the samples with a higher aspect ratio formed in a three-stage manner have an evident lower contact resistance. Highlights: Three-stage forming of micro channels of titanium bipolar plates was investigated. The limit forming height was improved for 42.4% comparing to single stage stamping. The effect of multistage forming on the thinning of sheet was revealed. The contact resistance with carbon paper decreases comparing to single stage samples.